Influence of slurry mass concentration on the mineralization capacity and mechanical properties of coal-based solid wastes - Jin, Feng; Wu, Xiaoru; Liu, Zhicheng; Pan, Hao; Shong, Tianqi (Frontiers in Materials, 2025)
The CO2-mineralized coal-based solid waste backfilling is an effective method for solid waste treatment and carbon sequestration. Both the carbon sequestration capacity, rheological properties and unconfined compressive strength (UCS) of the CO2-mineralized coal-based solid waste backfill material (CO2-CBM) are key evaluation indicators for its application and promotion. To optimize the engineering performance of CO2-CBM, the influence mechanism of slurry mass concentration (65%–73%) on its carbon sequestration capacity, rheological properties and UCS was systematically studied. Study results show that the carbon sequestration rate of CO2-CBM decreases with the increase of slurry mass concentration. Over a period of time, the carbon sequestration amount also decreases with the increase of slurry mass concentration, reaching 82.4 g/kg at the mass concentration of 65%. Both the extension of the standing time and the increase in mass concentration significantly rise the flow resistance of CO2-CBM. When the mass concentration is 73% and the standing time is 30 min, the yield stress and plastic viscosity of CO2-CBM reach 281.84 Pa and 0.95 Pa·s. The results of microscopic analysis show that due to the higher concentration of C-S-H in the slurry, CO2-CBM exhibits a denser structure and lower porosity. Consequently, as the slurry mass concentration increases, the UCS of the CO2-CBM is significantly improved, and the UCS reaches 3.30 MPa at the slurry mass concentration of 73% after a standing time of 28 days. This research provides a basis for optimizing key parameters for the co-processing of solid waste and CO2 in coal mine goaf.